Bloch equations for proton exchange reactions in an aqueous solution. (30th October 2017) - Lee, Jae‐Seung; Regatte, Ravinder R.; Jerschow, Alexej
Abstract: The extension of the Bloch equations for acid‐base reactions in an aqueous solution is revisited. The acid‐base reactions are second order, and several reactions catalyzed by distinct catalysts may happen simultaneously. By constructing pseudo first‐order reactions and assuming fast dissemination of protons from catalysts to solvent water, this extension converges to the well‐known Bloch‐McConnell equations for a two‐site first‐order exchange. Thus, explicit relationships between the parameters appearing in the reactions and the Bloch‐McConnell equations are established. The dependencies of exchange rates and chemical exchange saturation transfer effects on pH were numerically and experimentally investigated for representative examples.